'A Comparative Analysis of Regional Innovation Characteristics Using an Innovation Actor Framework. (March 2018) - Han, Sungho; Yoo, Gwang Min; Kwak, Sunjoo
Knowledge, a fundamental component of innovation, expands more effectively when innovation actors are in geographical proximity to each other. Innovation in each region is driven by innovation actors, and thus, the innovation capability of a region is directly linked to the activities of innovation actors in that region. In keeping with this perspective, this study was conducted in order to present the characteristics of the cross-regional innovation capability using an analytical framework of regional innovation actors, such as research institutes, technology intermediaries, universities and firms. In order to analyse the position of each Korean region's innovation actors, this study classified research subjects from the 2013 National Research and Development Investment Program Information into seven sub-categories and utilised them as the data for the analysis. Multiple factor analysis (MFA), which compresses the various indices effectively, was applied in order to classify the regions that have similar innovation actors into a small number of categories. Based on the factors derived from MFA, the innovation characteristics of sixteen regions were examined. The results showed that the innovation actors differ across regions, although Seoul, Gyeonggi and Daejeon are ahead of all other regions in terms of innovation activity. The policy implications of this analysis are as follows: first, the imbalance in the innovation capabilities among regions must be improved. Second, differentiated regional innovation policies are required because the innovator actors who lead regional innovation differ from region to region.